Education modifies the type of subjective memory complaints in older people. (25th May 2015) - Alagoa João, Ana; Maroco, João; Ginó, Sandra; Mendes, Tiago; de Mendonça, Alexandre; Martins, Isabel Pavão
Abstract : Objective: The aim of the study is to analyze the relationship between the level of education and the profile of subjective memory complaints (SMC). Methods: Participants were healthy volunteers aged >50 years old, from a community‐based sample. Educational attainment was self‐reported, and participants were subsequently assembled in four groups, according to the highest grade achieved in school. Additionally, they were questioned about their own memory abilities using an SMC scale (total score 0–21) and assessed for the presence of depressive symptoms. Results: A total of 841 participants aged 50–92 years old were included. The mean total score on the SMC scale was 5.3 ± 3.2, and 80.4% of the subjects reported at least one minor complaint about their memory. There was no correlation between total SMC score and higher educational level, even after accounting for the presence of depressive symptoms. However, regarding specific SMC, the use of notes to avoid forgetting was more frequent in higher levels of education, whereas the opposite trend was observed for complaints of transient confusion. Conclusion: Educational attainment possibly modulates the frequency and type of SMC in normal aging. Because these complaints are a major symptom for the diagnosis of cognitive decline, it seems relevant to consider the level of education when interpreting subjective reports on memory. Copyright © 2015 John Wiley & Sons, Ltd.